The Amoebic Growth of Project Costs - Eden, C.; Ackermann, Fran; Williams, T. (Project Management Institute, 2005)
In the public arena, we often hear about projects that have suffered massive cost overruns. Often they are related to large public construction projects such as airports, bridges, or public buildings. Large overruns also exist in private industry. However, often these do not appear in the newspapers, so the public is not as aware of them. Of course, not all projects go badly wrong, but quite a few do, and frequently we find ourselves uncertain of the causes for such overruns. In this paper, industrial projects that overrun and overrun in a surprising manner are considered. In other words, the paper considers those many projects where the extent of the overrun iswell beyond what might ever have been anticipated, even though what was going wrong within the projects was, for the most part, understood. The basis for the content of the paper (that is, the structure and lessons), are drawn from a postmortem analysis of many large projects as part of claims analysis, particularly “delay and disruption” claims for projects whose total expenditure appeared, at first look, inexplicable or surprising. The aim of the paper is to contribute to an understanding of how projects go badly wrong, when they do, and in particular to draw some lessons from this exploration that are likely to help all managers. The reasons for cost escalation are not just the responsibility of project managers.